Estudo de nanocompósitos poli(metacrilato de hidroxietila) / laponita para revestimento de sementes - Lima, Kelly Santana (2018)
The search for more productive seeds and with better transport and storage conditions has developed the interest of companies and researchers. In this section, nanotechnology, in particular, polymer / clay nanocomposites has proved to be an excellent alternative. By means of these nanomaterials it is possible to transport assets that allow the plant to better growth, productivity and germination rates, through the transport of fertilizers, agrochemicals or even essential micronutrients. The aim of this work was to synthesize and study nanocomposites polymer / clay; poly (hydroxyethyl methacrylate), pure laponite (pHEMA / Lap) and enriched with manganese micronutrients (pHEMA / LapMn). These materials aim to provide water and concomitantly provide nutrients to the seeds. The best formulation for the samples, amounts of polymer and clay was studied, and from this the micronutrient was incorporated into the formulation. The materials were characterized by absorption spectroscopy in the infrared region (FTIR), X-ray diffractometry (XRD) and thermogravimetry (TG). In addition, the water uptake capacity of the samples was evaluated. TG results showed an increase in thermal stability due to the interaction of the polymer chain with the clay. The XRD study showed that pure Lap and Lap Mn presented similar basal spacing to that found in the literature and that the nanocomposite had an exfoliated structure of the materials. The observation of the degree of swelling of the samples showed that the nanocomposites showed a capacity of water absorption 10% higher than the pure hydrogel. The seed coating affected the germination rate of the seeds, showing an optimization of this process.